2021
DOI: 10.1002/anie.202015215
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Dehydrogenases and N‐Heterocyclic Carbene Gold(I) Catalysts: Design of a Chemoenzymatic Cascade towards Optically Active β,β‐Disubstituted Allylic Alcohols

Abstract: The combination of gold(I) and enzyme catalysis is used in at wo-step approach, including Meyer-Schuster rearrangement of as eries of readily available propargylic alcohols followed by stereoselective bioreduction of the corresponding allylic ketone intermediates,toprovide optically pure b,b-disubstituted allylic alcohols.T his cascade involves ag old N-heterocyclic carbene and an enzyme,d emonstrating the compatibility of both catalyst types in aqueous medium under mild reaction conditions.T he combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Very recently, the Gotor-Lavandera group has described a sequential cascade combining a gold-mediated Meyer-Schuster rearrangement followed by subsequent asymmetric reduction to make chiral β,β-disubstituted allylic alcohols (Scheme 4c). [55] Besides Au-mediated alkyne hydration, in a collaboration between the groups of Turner and Greaney, a variant of the monoamine oxidase from Aspergillus niger (MAO-N D5) was used to make different iminium ions starting from N-alkyl tetrahydroisoquinolines (THIQs) followed by gold-catalysed CÀ C bond formation to access a set of C-(1) functionalised N-alkyl THIQs in high yields, under mild conditions and with no compartmentalisation required (Scheme 4d). [56]…”
Section: Recent Examples Of Synthetic Cascades Combining Other Tm-med...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the Gotor-Lavandera group has described a sequential cascade combining a gold-mediated Meyer-Schuster rearrangement followed by subsequent asymmetric reduction to make chiral β,β-disubstituted allylic alcohols (Scheme 4c). [55] Besides Au-mediated alkyne hydration, in a collaboration between the groups of Turner and Greaney, a variant of the monoamine oxidase from Aspergillus niger (MAO-N D5) was used to make different iminium ions starting from N-alkyl tetrahydroisoquinolines (THIQs) followed by gold-catalysed CÀ C bond formation to access a set of C-(1) functionalised N-alkyl THIQs in high yields, under mild conditions and with no compartmentalisation required (Scheme 4d). [56]…”
Section: Recent Examples Of Synthetic Cascades Combining Other Tm-med...mentioning
confidence: 99%
“…Due to compatibility issues, the Au/carbene catalyst (IPrAuOTf) was encapsulated in mesoporous silica, allowing the efficient implementation of both steps in the same vessel. Very recently, the Gotor‐Lavandera group has described a sequential cascade combining a gold‐mediated Meyer‐Schuster rearrangement followed by subsequent asymmetric reduction to make chiral β,β‐disubstituted allylic alcohols (Scheme 4c) [55] …”
Section: Linear Cascades Combining Transition Metal Catalysis and Bio...mentioning
confidence: 99%
“…Ketones comprising one large and one small substituent at the carbonyl group are very common substrates for ADH-catalysed reductions. Especially methyl ketones are popular starting materials and a broad range of aliphatic (Sinha and Keinan, 1997), aromatic (Hamada et al, 2001;Stampfer et al, 2002;Hummel et al, 2003;Gonzalez-Martinez et al, 2019;Bandeira et al, 2020), and conjugated ketones (Schubert et al, 2001;Sgalla et al, 2007;Albarrán-Velo et al, 2020;González-Granda et al, 2021) have been reported. Figure 11 shows a representative selection of chiral alcohols obtained from the reduction of methyl ketones.…”
Section: Adh-catalysed Reduction Reactionsmentioning
confidence: 99%
“…[345][346][347][348] Several examples are paving the way toward the merging of enzymes with chemical methods in elaborated (cascade) synthesis. [349][350][351][352][353] Finally, the growing importance of (meta)genomics and ultrahigh-throughput screening, such as seen with microfluidic approaches, 354 will raise new challenges. Generating large data set from vast and diverse protein libraries is not technically limited anymore, instead the interpretation of the rapidly growing amount of information remains currently an obstacle to advancing further and faster.…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%